2009
DOI: 10.1002/ccd.22172
|View full text |Cite
|
Sign up to set email alerts
|

New onset atrial fibrillation after patent foramen ovale closure

Abstract: The number of patients in whom atrial fibrillation was detected was relatively low. It is often a self-limited complication of PFO closure that may occur more frequently in elderly patients and those treated with the STARFlex device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 135 publications
6
59
0
Order By: Relevance
“…The CardioSEAL and STARFlex occluders (NMT Medical, Boston, MA) were combined into one group due to their structural similarities, consistent with prior studies. [24][25][26][27] Data from agitated saline studies were available postprocedure and at 3-month and 1-year follow-up. As a secondary analysis to determine the time course of residual shunt, the rates of detected interatrial shunting were compared at each time point using the McNemar test.…”
Section: Methodsmentioning
confidence: 99%
“…The CardioSEAL and STARFlex occluders (NMT Medical, Boston, MA) were combined into one group due to their structural similarities, consistent with prior studies. [24][25][26][27] Data from agitated saline studies were available postprocedure and at 3-month and 1-year follow-up. As a secondary analysis to determine the time course of residual shunt, the rates of detected interatrial shunting were compared at each time point using the McNemar test.…”
Section: Methodsmentioning
confidence: 99%
“…This table also demonstrates the 'quality score' assigned based on the number of factors matched. Five studies matched ≥5 factors scoring 3 points for quality [16,[35][36][37]39]. In this group the OR for prevalence of post-closure AFIB was 0.44 (95% CI 0.26-0.75), using a fixed-effect model.…”
Section: Sensitivity Analysis Using Study Quality Assessmentmentioning
confidence: 99%
“…New‐onset periprocedural AF is a known complication of percutaneous PFO closure with an incidence of up to 3.9% from a large series of 1349 patients who underwent PFO closure 89. In the RESPECT (Long‐Term Outcomes) trial, new‐onset AF was detected in 1.2% in the closure group and only 0.8% in the medical therapy group ( P =0.753; Table 5).…”
Section: Complications Of Pfo Closurementioning
confidence: 99%
“…25 The CLOSE trial reported an incidence of 2.5% in patients who underwent PFO closure,27 whereas the REDUCE trial reported an incidence of 6.6% for any AF or atrial flutter and 2.3% for serious AF or atrial flutter 26. In a large series by Staubach, among patients who developed new‐onset AF post PFO closure, 62.3% were detected within 4 weeks and 15% between 4 weeks to 6 months post‐procedure 89. The exact mechanism of new‐onset AF after PFO closure is not known, but several hypotheses have been suggested.…”
Section: Complications Of Pfo Closurementioning
confidence: 99%